Transforming the curriculum through the arts - Gibson, R.; Ewing, Robyn (South Yarra, Vic. : South Yarra, Vic., 2011)
There is much evidence to suggest that the Arts can make a unique contribution to the lives of young people, their learning and their ability to be creative and imaginative thinkers. Transforming the Curriculum through the Arts supports this idea by presenting the Arts as being central to children's development
Includes index and reference.
Keywords: Arts in education -- Australia; Arts -- Study and teaching -- Australia; Curriculum change -- Australia